Trypanosomatid histones: The building blocks of the epigenetic code of highly divergent eukaryotes - Ocampo, Josefina (2025)
Histones play a fundamental role in eukaryotic organisms not only as scaffolding proteins in DNA packaging but also in regulating gene expression. They constitute the protein reel around which DNA wraps forming nucleosomes. This initial packing gives rise to the chromatin fiber which is next folded into three-dimensional arrangements. Additionally, histones have expanded their functions through the emergence of histone variants which have specialized purposes and can deeply affect chromatin organization and dynamics. Moreover, both canonical histones and histone variants comprise the building blocks of the histone code by being targets of different post-translational modifications (PTMs) that occur in a highly regulated manner both in place and time. Most of the above-mentioned about chromatin organization is conserved among eukaryotes. However, trypanosomatid histones have many peculiarities that entail a special description. In this review, we compile the current knowledge of canonical core histones, histone variants, and their PTMs in trypanosomatids. We highlight the similarities and differences between histone variants and their canonical counterparts in trypanosomatids, and we compare them with those from model organisms. Finally, we discuss the crosstalk between different histone marks and their genomic distribution underlying the uniqueness of trypanosomatids.